2006
DOI: 10.1093/nar/gkl145
|View full text |Cite
|
Sign up to set email alerts
|

THUMP from archaeal tRNA:m22G10 methyltransferase, a genuine autonomously folding domain

Abstract: The tRNA:m22G10 methyltransferase of Pyrococus abyssi (PAB1283, a member of COG1041) catalyzes the N2,N2-dimethylation of guanosine at position 10 in tRNA. Boundaries of its THUMP (THioUridine synthases, RNA Methyltransferases and Pseudo-uridine synthases)—containing N-terminal domain [1–152] and C-terminal catalytic domain [157–329] were assessed by trypsin limited proteolysis. An inter-domain flexible region of at least six residues was revealed. The N-terminal domain was then produced as a standalone protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…Our results indicate that the THUMP domain alone is not sufficient for tRNA binding. A similar observation was made by Gabant et al (2006) on the THUMP domain of archaeal TrmG10. Also, the individual MTase domain does not show any tRNA binding.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results indicate that the THUMP domain alone is not sufficient for tRNA binding. A similar observation was made by Gabant et al (2006) on the THUMP domain of archaeal TrmG10. Also, the individual MTase domain does not show any tRNA binding.…”
Section: Discussionsupporting
confidence: 81%
“…The Trm1 enzyme bears a putative helix-turn-helix motif at its C terminus, while the TrmG10 protein contains an N-terminal THUMP domain (Armengaud et al 2004). The THUMP domain, present in thiouridine synthases, RNA MTases, and pseudouridine synthases (Aravind and Koonin 2001), was proposed to interact with a specific region of the tRNA, thereby targeting the catalytic domain of the enzyme toward a particular region of the tRNA structure (Gabant et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been no reports confirming the interaction between the THUMP domain and RNA, although it is found in several RNA modification enzymes and is therefore likely to serve as a general module for interaction with RNA (Aravind and Koonin 2001;Gabant et al 2006). The present study is the first to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…Spectral changes in this region were reported to indicate conformational changes of nucleic acid molecules (Connor et al 1994;Gray et al 1995;Nejedly et al 2005;Saito et al 2008). Gabant et al (2006) reported for ThiI and other tRNA modification enzymes that some conformational Phe and (B) TPHE39A: (lanes 1,5,9) 100 pmol protein; (lanes 2,6,10) 100 pmol RNA; (lanes 3,7,11) 100 pmol protein + 100 pmol RNA; and (lanes 4,9,12) 200 pmol protein + 100 pmol RNA. RT ln K A = DH À TDS.…”
Section: Structural Changes In Rna Over Binding With Thiimentioning
confidence: 99%
See 1 more Smart Citation